18β-glycyrrhetinic acid inhibited mitochondrial energy metabolism and gastric carcinogenesis through methylation-regulated TLR2 signaling pathway. (26th October 2018) - Cao, Donghui; Wu, Yanhua; Jia, Zhifang; Zhao, Dan; Zhang, Yangyu; Zhou, Tianyu; Wu, Menghui; Zhang, Houjun; Tsukamoto, Tetsuya; Oshima, Masanobu; Jiang, Jing; Cao, Xueyuan
Abstract: The natural phenolic substance, 18β-glycyrrhetinic acid (GRA), has shown enormous potential in the chemoprevention of cancers with rich resources and biological safety, but the GRA-regulated genetic and epigenetic profiles are unclear. Deregulated mitochondrial cellular energetics supporting higher adenosine triphosphate provisions relative to the uncontrolled proliferation of cancer cells is a cancer hallmark. The Toll-like receptor 2 (TLR2) signaling pathway has emerged as a key molecular component in gastric cancer (GC) cell proliferation and epithelial homeostasis. However, whether TLR2 influenced GC cell energy metabolism and whether the inhibition effects of GRA on GC relied on TLR2 signaling were not illustrated. In the present study, TLR2 mRNA and protein expression levels were elevated in gastric tumors in the K19-Wnt1/C2mE (Gan) mice model, GC cell lines and human GCs, and the overexpression of TLR2 was correlated with the high histological grade and was a poor prognostic factor in GC patients. Further gain and loss of function showed that TLR2 activation induced GC cell proliferation and promoted reactive oxygen species (ROS) generation, Ca 2+ accumulation, oxidative phosphorylation and the electron transport chain, while blocking TLR2 inhibited mitochondrial function and energy metabolism. Furthermore, GRA pretreatment inhibited TLR2-activated GC cell proliferation, energy metabolism and carcinogenesis. In addition, expression of TLR2 was found to be downregulated by GRA through methylation regulation. Collectively, the results demonstrated that GRA inhibited gastric tumorigenesis through TLR2-accelerated energy metabolism, suggesting GRA as a promising therapeutic agency targeting TLR2 signaling in GC. Abstract : The study elucidated the inhibitory effects and mechanisms of 18β-GRA. Using transgenic GC model, cell lines and patients, TLR2, a poor prognostic factor in GC, was firstly identified as a potential GRA target regulating mitochondrial energy metabolism.